(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the medication adherence rate for hypertension treatment in Vietnam and to investigate the associated factors. Research methods: A search was conducted from January 2023 to August 2024 across 26 Vietnamese articles from 3 regions of Vietnam. Results: Analysis revealed a medication adherence rate of 62% (95%CI: 0.54-0.70) among hypertensive patients. Adherence rates were 61% in the North, 59% in the Central region, and 65% in the South. Regarding gender, men exhibited a lower adherence rate of 48% compared to 56% for women. The compliance rate of patients in urban areas (76%) is higher than in rural areas (67%). Patients with a disease duration of more than 5 years had lower medication adherence (70%) than the group with a disease duration of 5 years or less (77%). Conclusions: The medication compliance rate of people with hypertension in Vietnam is relatively high. Region, age, gender, patient’s place of residence, and duration of hypertension are factors related to medication compliance.